ACCOUNTING AND FINANCIAL REPORTING AS A TOOL FOR TRANSPARENCY OF ECONOMIC ACTIVITY OF A BUSINESS ENTITY - IGOR Mizikovsky; ALEXANDER Bazhenov (Учёт. Анализ. Аудит, 2019)
This paper proves that accounting and financial reporting is one the main tools for effective economic decision-making and, therefore, for transparency of economic activity of a business entity. When generating accounting and financial reports it is necessary to follow three basic principles: fairness, completeness and neutrality of the information disclosed. Compilation of accounting and financial statements involve two stages: first, the preparation stage where special attention should be paid to the information component (accounting records, inventory take) to compile accounting and financial statements and second, the stage of the very generation of the accounting and financial statements. The objective of the latter stage is to follow all the obligatory accounting norms and regulations eliminating material misstatements.